Innovative Technologies in Teachingdirectors and Specialists of Industrial Enterprises on "Labor Protection" - Dustkabilovich, Rakhimov Oktyabr; o`g`li, Muradov Sirojiddin Husan (European Journal of Life Safety and Stability (2660-9630), 2021)
The article clearly illustrates the information on innovative pedagogical technologies and interactive methods of teaching directors and specialists of enterprises, organizations and institutions labor protection course, and provides a classification defined by the authors.The course of labor protection covers modular teaching technology and ways of using interactive methods in teaching.In order to make suree that the course does not directly affect the work and save the time of specialists, it is recommended to conduct training of directors and specialists on labor protection on the basis of online digital modular technology.